Work Stress and Influencing Factors - Siti Rukhayati; Titi Prihatin (Solo International Collaboration and Publication of Social Sciences and Humanities, 2023)
This article discusses work stress. Stress is a condition of tension that affects emotions, thought processes, and one's condition. Stress can happen to anyone at any time because stress is a part of human life. The research method uses a type of qualitative research and literature study, the approach uses content analysis and induction. The results of the study concluded that stress is influenced by environmental factors, organizational factors, and individual factors. Stress can have a positive as well as a negative impact. Work stress is a very important aspect of the organization, especially its relation to employee productivity. Therefore work stress in the work environment must be anticipated. If the performance of employees is good then the organization will be easy to achieve its goals.